Governing knowledge for development: Knowledge clusters in Brunei Darussalam and Malaysia - Syamimi Ariff; Hans-Dieter Evers; Anthony Banyouko Ndah; Farah Purwaningrum (University of Bonn, Center for Development Research (ZEF), 2014)
With the dwindling of natural resources, like oil and gas, even resource-rich countries like Brunei Darussalam and Malaysia have to re-adjust their development strategies. Governing knowledge for development (K4D) is seen as a way out of the dilemma of reduced revenues from natural resources. This paper analyses the attempts to create knowledge clusters as a strategy to move Brunei and Malaysia towards knowledge-based economies. Our study shows that several knowledge clusters have already been established in Peninsular Malaysia and are starting to emerge in Brunei Darussalam. The paper is structured as follows: the first section explains the dangers of falling into a "knowledge trap" and the strategies a country may adopt to govern knowledge. The second section looks at the epistemic landscapes in Peninsular Malaysia. Two knowledge clusters are the focal points of analysis, namely the North Corridor-Penang Knowledge Cluster and the Multimedia Super Corridor (MSC-Cyberjaya) Knowledge Cluster. We then provide empirical evidence of knowledge cluster formation in Brunei Darussalam as an effort to build up knowledge institutions and to diversify its economy. The paper ends with recommendations how to build the basis for a move towards a knowledge-based economy.
Keywords: 330; knowledge governance; knowledge cluster; development strategies; Malaysia; Brunei Darussalam